The Usage of Kinship Terms Across Three Generations in Indonesia - Idaryani Idaryani (Journal of English Language and Education, 2023)
The study aims to find out 1) how is the usage of kinship terms among Acehnese people across three generations (generation 1, generation 2, and generation 3)? 2) what is the parents’ perspective (G1s and G2s) on the usage of kinship terms, and 3) how are the roles of parents on the usage of kinship terms to their children. The study employs qualitative method. The data collected from observations and interviews. The participants are from two villages in outskirt of the Lhokseumawe city, Aceh, Indonesia.  The participants of the study are 3 families from each village. Therefore, there were 18 participants involved in the study. The results of the study show that the usage of kinship terms across three generations are active except for particular kinship terms. The usage of particular kinship terms among G2 starts shifting to Indonesian language. The usage of particular kinship terms among G3 has been shifted to Indonesian language.